Prediction of Mortality in Patients on Peritoneal Dialysis Based on the Fibrinogen Mannosylation - Marko Baralić; Lucia Pažitná; Voin Brković; Mirjana Laušević; Nikola Gligorijević; Jaroslav Katrlík; Olgica Nedić; Dragana Robajac (Cells, 2023)
As we already reported, fibrinogen fucosylation emerged as a prognostic marker of peritoneal membrane function in end-stage renal disease (ESRD) patients on peritoneal dialysis. After a follow-up period of 18 months, we estimated the ability of employed lectins, as well as other biochemical parameters, to serve as mortality predictors in these patients. Following a univariate Cox regression analysis, ferritin, urea clearance, residual diuresis, hyperglycemia, and an increase in the signal intensity obtained with Galanthus nivalis lectin (GNL) emerged as potential mortality predictors, but additional multivariate Cox regression analysis pointed only to glucose concentration and GNL as mortality predictors. Higher signal intensity obtained with GNL in patients that died suggested the importance of paucimannosidic/highly mannosidic N-glycan structures on fibrinogen as factors that are related to unwanted cardiovascular events and all-cause mortality and can possibly be seen as a prediction tool. Altered glycan structures composed of mannose residues are expected to affect the reactivity of mannosylated glycoproteins with mannose-binding lectin and possibly the entire cascade of events linked to this lectin. Since patients with ESRD are prone to cardiovascular complications and the formation of atherosclerotic plaques, one can hypothesize that fibrinogen with increasingly exposed mannose residues may contribute to the unwanted events.